2012
DOI: 10.1002/ana.22668
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of highly prevalent brain ischemia in intracerebral hemorrhage

Abstract: Objective To determine the prevalence, characteristics, risk factors and temporal profile of concurrent ischemic lesions in patients with acute primary intracerebral hemorrhage (ICH). Methods Patients were recruited within a prospective, longitudinal, magnetic resonance imaging (MRI) based study of primary ICH. Clinical, demographic, and MRI data were collected on all subjects at baseline and 1 month. Results Of the 138 patients enrolled, mean age was 59 years, 54% were male, 73% black, and 84% had a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
169
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(182 citation statements)
references
References 15 publications
11
169
0
2
Order By: Relevance
“…Pneumonia was uncommon and not associated with delirium in this cohort. Cerebral ischemia is common after ICH (33,34), might be an underlying risk factor for delirium, and deserves future study.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia was uncommon and not associated with delirium in this cohort. Cerebral ischemia is common after ICH (33,34), might be an underlying risk factor for delirium, and deserves future study.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of an ICH is not only restricted to the primary site of injury, but also identified in the remote regions (MunBryce et al 2004;Menon et al 2012). But the pathophysiological mechanisms of the remote effects of hematoma remain unknown, despite the important implications for both prognosis and treatment in the clinical practice of ICH.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, more recent MR imaging studies have suggested that subacute ischemic injury occurs in areas remote from the hematoma, including borderzone (BZ, also known as watershed) regions. [6][7][8][9][10][11] The etiology of these ischemic injuries has been postulated to be hemodynamic compromise secondary to BP reduction. 10 Studies of CBF in the perihematoma region indicate that this region is relatively hypoperfused, but not se-verely enough to result in ischemia.…”
Section: Abbreviationsmentioning
confidence: 99%
“…[6][7][8][9][10][11] The etiology of these ischemic injuries has been postulated to be hemodynamic compromise secondary to BP reduction. 10 Studies of CBF in the perihematoma region indicate that this region is relatively hypoperfused, but not se-verely enough to result in ischemia. [12][13][14] Previous PET studies have demonstrated that the perihematoma region is, in fact, hypometabolic, likely secondary to the primary brain injury, and that the oxygen extraction fraction is not elevated, indicating the absence of misery perfusion.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation